Revaluation of collagenic protein from mahi-mahi (Coryphaena hippurus) residues by extraction of superior quality gelatin - Romero-Santivañez, Renzo (2023)
The aim of this work was to optimize the conditions for gelatine extraction from mahi-mahi (Coryphaena hippurus) skin using a five-level central composite design using the response surface methodology. The effects of extraction temperature (40-70 °C), extraction time (60-400 min), and citric acid concentration (0.1-0.9%) on gel strength (g) and protein yield (%) were evaluated. The optimal extraction conditions were 56.8 °C, 331 min and 0.26% citric acid. The experimental values of the responses were 387 ± 4.5 g gel strength and 20.4 ± 0.08% protein yield. The gelatine obtained was characterized and the results showed a high protein content (88.3%) and low ash content (1.0%). The main amino acid was glycine (20.9%) and the content of imino acids (proline and hydroxyproline) was 18.7%, while the content of essential amino acids was 22.35 g/100 g of protein. The values of the gelation and melting points were 17.6 and 25.6 °C, respectively. The viscosity at 60 °C was 11.0 cP and the pH value was 4.9. Mahi-mahi skin gelatine meets the physical and chemical requirements for an edible gelatine.